Comparing apples with oranges? An approach to link TIMSS and the National Educational Panel Study in Germany via equipercentile and IRT methods. (December 2015) - Nissen, Annika; Ehmke, Timo; Köller, Olaf; Duchhardt, Christoph
Highlights: The mathematical frameworks of NEPS and TIMSS have a high overlap. For NEPS, both linking methods provide reliable score equivalents in TIMSS metric. Results are valid for a population level but not for individual students. Abstract: The aim of this linking study is to classify the National Educational Panel Study (NEPS) according to the criterion based reference frame of the Trends in International Mathematics and Science Study (TIMSS). One requirement for a strong linking is a high conceptual overlap of the frameworks. The results of the comparison between NEPS and TIMSS indicate a high overlap. To link the studies the equipercentile equating and an IRT linking approach are compared. The results show that both methods showed similar descriptive statistics and satisfying classification consistency. Nevertheless, the equipercentile equating has small advantages and is therefore more suitable. Thus, inferences are possible on a population level, but the results should not be reported or interpreted on an individual level.